(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Allergic rhinitis, commonly referred to as hay fever, is an IgE-mediated inflammatory condition of the nasal mucosa. It is characterized by symptoms such as sneezing, nasal blockage, nasal itching, and watery eyes. Common allergens include pollen, pet dander, mold, insects, and house dust. This study aimed to assess the demographic characteristics, clinical manifestations, and triggering factors among patients with allergic rhinitis attending a tertiary care center. Methods: A retrospective review was conducted on patients presenting to the outpatient ENT Clinic at Bangladesh Medical University (BMU), Bangladesh, from 1 January, 2020 to 31 December, 2021. Results: A total of 320 patients were included, whom 59.7% were male and 40.3% were female. The age group18-30years was the most frequently affected. Perennial rhinitis was observed in 65% of cases. House dust was the predominant triggering factor, identified in 37.5% of patients. Symptoms were predominantly severe, sneezing (31.3%) and nasal blockage (20.3%) were the most common complaints in their severe form. Conclusion: This study found a slight male predominance (59.7%) among patients with allergic rhinitis. Sneezing and nasal blockage emerged as the most frequent and severe symptoms. House dust was the leading trigger, highlighting the need for targeted environmental control measures in this population. Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 42-46